Chlorovirus ATCV-1 Accelerates Motor Deterioration in SOD1-G93A Transgenic Mice and Its SOD1 Augments Induction of Inflammatory Factors From Murine Macrophages - Petro, Thomas M.; Agarkova, Irina V.; Esmael, Ahmed; Dunigan, David D.; Van Etten, James L.; Pattee, Gary L. (Frontiers in Neurology, 2022)
Background Genetically polymorphic Superoxide Dismutase 1 G93A (SOD1-G93A) underlies one form of familial Amyotrophic Lateral Sclerosis (ALS). Exposures from viruses may also contribute to ALS, possibly by stimulating immune factors, such as IL-6, Interferon Stimulated Genes, and Nitric Oxide. Recently, chlorovirus ATCV-1, which encodes a SOD1, was shown to replicate in macrophages and induce inflammatory factors. Objective This study aimed to determine if ATCV-1 influences development of motor degeneration in an ALS mouse model and to assess whether SOD1 of ATCV-1 influences production of inflammatory factors from macrophages. Methods Sera from sporadic ALS patients were screened for antibody to ATCV-1. Active or inactivated ATCV-1, saline, or a viral mimetic, polyinosinic:polycytidylic acid (poly I:C) were injected intracranially into transgenic mice expressing human SOD1-G93A- or C57Bl/6 mice. RAW264.7 mouse macrophage cells were transfected with a plasmid vector expressing ATCV-1 SOD1 or an empty vector prior to stimulation with poly I:C with or without Interferon-gamma (IFN-γ). Results Serum from sporadic ALS patients had significantly more IgG1 antibody directed against ATCV-1 than healthy controls. Infection of SOD1-G93A mice with active ATCV-1 significantly accelerated onset of motor loss, as measured by tail paralysis, hind limb tucking, righting reflex, and latency to fall in a hanging cage-lid test, but did not significantly affect mortality when compared to saline-treated transgenics. By contrast, poly I:C treatment significantly lengthened survival time but only minimally slowed onset of motor loss, while heat-inactivated ATCV-1 did not affect motor loss or survival. ATCV-1 SOD1 significantly increased expression of IL-6, IL-10, ISG promoter activity, and production of Nitric Oxide from RAW264.7 cells. Conclusion ATCV-1 chlorovirus encoding an endogenous SOD1 accelerates pathogenesis but not mortality, while poly I:C that stimulates antiviral immune responses delays mortality in an ALS mouse model. ATCV-1 SOD1 enhances induction of inflammatory factors from macrophages.